The structural metaphorical abstraction in Adrian Arleo's sculptural ceramics - Nisreen Samir Ghudir; Sabah ahmed hussin (Basrah Arts Journal, 2024)
This research delves into the philosophical concept of compositional metaphor and its artistic application, particularly in the works of the ceramic artist Adrian Aurelio. It aims to illustrate how compositional metaphor serves as a conduit for conveying philosophical insights and profound meanings through art. The structure of the research comprises four chapters. The initial chapter (General Framework) addresses the research problem encapsulated in the question: "How was compositional metaphor activated to achieve ceramic output, and what visual elements did the ceramist employ in realizing these compound metaphors?" The research aims to identify compositional metaphor and its application mechanisms in the sculptural ceramics of Adrian Aurelio. The second chapter (Theoretical Framework) encompasses two sections. The first section examines the concept of metaphor and compositional metaphor, while the second section explores the artistic outputs of the ceramicist Adrian Aurelio. The third chapter (Research Procedures) delineates the research's scope, selecting four artistic works for analysis. The fourth chapter presents the results and conclusions. Among the key findings is the ceramist's adeptness in reaching a level of expressive semantic encoding through her sculptural ceramic discourse. She amalgamated fragments of the same gender (human parts) to create a human figure, rendering the pieces complementary to each other, inviting interpretative narrative readings that mirror reality with profound connotations. Compositional metaphor, therefore, emerges as a conscious construct, intertwining artistic vision with technology and culture. This fusion engenders aesthetic innovation and serves as a conduit for expressing her philosophy and societal concerns, amalgamating diverse components to formulate multi-layered messages pertaining to environmental, cultural, and social realms.